2(-4x+9y+6xy)-5(2x+8y)=

Simple and best practice solution for 2(-4x+9y+6xy)-5(2x+8y)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(-4x+9y+6xy)-5(2x+8y)= equation:


Simplifying
2(-4x + 9y + 6xy) + -5(2x + 8y) = 0

Reorder the terms:
2(-4x + 6xy + 9y) + -5(2x + 8y) = 0
(-4x * 2 + 6xy * 2 + 9y * 2) + -5(2x + 8y) = 0
(-8x + 12xy + 18y) + -5(2x + 8y) = 0
-8x + 12xy + 18y + (2x * -5 + 8y * -5) = 0
-8x + 12xy + 18y + (-10x + -40y) = 0

Reorder the terms:
-8x + -10x + 12xy + 18y + -40y = 0

Combine like terms: -8x + -10x = -18x
-18x + 12xy + 18y + -40y = 0

Combine like terms: 18y + -40y = -22y
-18x + 12xy + -22y = 0

Solving
-18x + 12xy + -22y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '22y' to each side of the equation.
-18x + 12xy + -22y + 22y = 0 + 22y

Combine like terms: -22y + 22y = 0
-18x + 12xy + 0 = 0 + 22y
-18x + 12xy = 0 + 22y
Remove the zero:
-18x + 12xy = 22y

Combine like terms: 22y + -22y = 0
-18x + 12xy + -22y = 0

Factor out the Greatest Common Factor (GCF), '2'.
2(-9x + 6xy + -11y) = 0

Ignore the factor 2.

Subproblem 1

Set the factor '(-9x + 6xy + -11y)' equal to zero and attempt to solve: Simplifying -9x + 6xy + -11y = 0 Solving -9x + 6xy + -11y = 0 Move all terms containing x to the left, all other terms to the right. Add '11y' to each side of the equation. -9x + 6xy + -11y + 11y = 0 + 11y Combine like terms: -11y + 11y = 0 -9x + 6xy + 0 = 0 + 11y -9x + 6xy = 0 + 11y Remove the zero: -9x + 6xy = 11y The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| x-.15x=20600 | | -3=-14+x | | 4x-12+1=-7x-12+1 | | 2(2p+3)=p+9 | | -4(x-3)-x-5=-5(x+6)+13 | | 9+-3x=8x+-3x | | 18x-12=8x+16 | | 2760.25/x=2.41 | | 2(2n+1)=3n+8 | | -x-3+4+2x-5=0 | | (6x^4/y)^2 | | 5-2x-3x-7=0 | | 1+-5x=5+8x | | 15(v+4)-3v=4(3v+3)-17 | | g(x)=1/3f(x-4) | | LN=3x+25 | | -0.10(126)+0.90x=0.05(x-14) | | 3x^2=-10x-6 | | 57-3n=21 | | 7[z-(5z+18)+2]=3(z+4) | | -2p-4(3-2p)=2(p-3)-14 | | 2(v+3)=9+v | | n^2+8n-73=-9 | | 9x+9v+8z-6y=xvzy | | 56/16 | | 56*1/16 | | http://media.apexlearning.com/Images/201305/30/9732b49e-38a0-4a46-8791-c144f128dfa4.gif | | c=20*5+100 | | c=30*5+50 | | 1.75m=4 | | X^2/11 | | x^2-2y-24=0 |

Equations solver categories